2007
DOI: 10.2174/138161207781757060
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between Stereochemistry and Biological Activity of Platinum(II) Complexes Chelated with Chiral Diamine Ligands: An Intricate Problem

Abstract: Abstract:The origin of activity differences between stereoisomers of anticancer platinum(II) complexes chelated with chiral diamine ligands has been almost exclusively explained by diastereoselective interactions with DNA. Although this model has been widely accepted in vitro and in vivo experiments showed some conflicting results, leading to the conclusion that other biomolecules might be responsible for this stereoselectivity as well. These compounds, called bionucleophiles, are in most instances amino acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 64 publications
(81 reference statements)
0
15
0
Order By: Relevance
“…1 Since double-helical DNA has a chiral structure, the stereochemistry of the adducts formed with complexes containing enantiomeric ligands can influence the antitumor activity. [3][4][5] Moreover, it is interesting to point out that three out of the six platinum compounds (namely oxaliplatin, lobaplatin and heptaplatin) approved for clinical use have a chiral structure (see Chart 1). The negligible difference generally observed for the biological activities of the enantiomers was related to the free rotation that offset any stereospecificity in the interactions with biological substrates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Since double-helical DNA has a chiral structure, the stereochemistry of the adducts formed with complexes containing enantiomeric ligands can influence the antitumor activity. [3][4][5] Moreover, it is interesting to point out that three out of the six platinum compounds (namely oxaliplatin, lobaplatin and heptaplatin) approved for clinical use have a chiral structure (see Chart 1). The negligible difference generally observed for the biological activities of the enantiomers was related to the free rotation that offset any stereospecificity in the interactions with biological substrates.…”
Section: Introductionmentioning
confidence: 99%
“…2 Early studies carried out for compounds cis-[PtX 2 A 2 ] (A = amine ligand and X = anionic ligand), indicated that the activity decreases in the order A = NH 3 > RNH 2 > R 2 NH, and, therefore, most investigations concerning chiral monodentate ligands were restricted to platinum complexes with primary amines. 1,5 On the other hand, cycloplatinated complexes have raised great interest as anticancer agents, 6,7 and compounds containing either bidentate [C,N] [8][9][10][11][12][13][14][15][16][17][18][19][20][21] or terdentate [C,N,N′] [22][23][24][25][26][27] ligands have been tested against tumor cells with very promising results. The degree of rotational freedom can be reduced using chelate ligands, an outstanding example being oxaliplatin, a third generation anti-cancer drug containing trans-1R,2R-diaminocyclohexane.…”
Section: Introductionmentioning
confidence: 99%
“…Dufrasne and Galanski [4] present the case of platinum complexes. The authors discuss the mode of interaction with DNA of anticancer platinum(II) complexes and their relevant pharmacological effects.…”
Section: Editorial: Target Specificity Of Effective Anticancer Therapmentioning
confidence: 99%
“…Furthermore, bulk of investigative results have demonstrated that the stereochemistry of the diamine ligands of platinum compounds with chiral C-substituted ethylenediamines had an important influence on their interactions of DNA, anticancer activity, toxicity, and resistance. 25,26 Particularly, it has been reported that optically pure (1,2-diarylethane-1,2-diamine)dichloroplatinum(II) complexes induce significant inhibitory effects on the growth of leukemic and tumor cells, and a distinctly better effect was generally observed with the R,R/S,S configurations compared with the R,S counterparts. [27][28][29][30] These results motivated us to apply the findings from platinum(II) complexes to iridium(III) complexes.…”
Section: Introductionmentioning
confidence: 99%